Relationship between cesarean section and early initiation of breastfeeding in Indonesia - Gayatri, Maria (Universitas Udayana, 2022)
Background and purpose: Breastfeeding initiation is internationally recommended due to its benefits on maternal and child health. The study aims to determine the relationship between mode of delivery and early breastfeeding initiation among women who delivered in health facilities. Methods: The study was based on The Indonesia Demographic and Health Survey 2017. There were 5,369 women whose children were born in the last 24 months preceding the survey in health facilities in Indonesia. Descriptive statistics and binary logistic regression were used for data analysis. The complex sample design was performed for analyses. Results: Of the women who had given birth to at least 24 months preceding the survey in health facilities, 57 percent of women were found to practice breastfeeding initiation. The likelihood of breastfeeding initiation among women who delivered in health facilities was associated with mode of delivery, which women with cesarean delivery (OR=0.33; 95%CI: 0.29-0.38) were less likely to practice breastfeeding initiation compared with those with normal vaginal delivery after adjusted by socio-economic factors. Moreover, women aged 35-49 years and non-working women were found to have higher probabilities to practice breastfeeding initiation. Conclusion: Maternal age, working status, and type of delivery were significantly influencing the practice of early initiation of breastfeeding among women who delivered in health facilities. Policy and intervention to encourage and support early initiation of breastfeeding should be taken into consideration by public health professionals and health providers. Comprehensive breastfeeding counseling should be a part of health care training to encourage moms to start nursing as soon as possible, especially for mothers who have caesarean deliveries. It is important to ensure the implementation of breastfeeding policy on the company’s worksite support policy.